Fractional nitric oxide measurement in exhaled air (FeNO): perspectives in the management of respiratory diseases - Beatrice Ragnoli; Alessandro Radaeli; Patrizia Pochetti; Stefano Kette; Jaymin Morjaria; Mario Malerba (SAGE Publishing, 2023)
Exhaled nitric oxide (NO) production, upregulated by inflammatory cytokines and mediators in central and peripheral airways, can be easily and non-invasively detected in exhaled air in asthma and other respiratory conditions as a promising tool for disease monitoring. The American Thoracic Society and European Respiratory Society released recommendations that standardize the measurement of the fractional exhaled NO (FeNO). In asthma, increased FeNO reflects eosinophilic-mediated inflammatory pathways and, as a biomarker of T2 inflammation can be used to identify asthma T2 phenotype. In this setting its measurement has shown to be an important tool especially in the diagnostic process, in the assessment and evaluation of poor adherence or predicting positive response to inhaled corticosteroids treatment, in phenotyping severe asthma patients and as a biomarker to predict the response to biologic treatments. The discovery of the role of NO in the pathogenesis of different diseases affecting the airways and the possibility to estimate the predominant site of increased NO production has provided new insight on its regulatory role in the airways, making it suitable for a potential extended use in clinical practice for different pulmonary diseases, even though its role remains less clear than in asthma. Monitoring FeNO in pulmonary obstructive lung diseases including chronic bronchitis and emphysema, interstitial lung diseases, obstructive sleep apnea and other pulmonary diseases is still under debate but has opened up a window to the role NO may play in the management of these diseases. The use of FeNO is reliable, cost effective and recommendable in both adults and children, and should be implemented in the management of patients with asthma and other respiratory conditions.